Health-related quality-of-life results from the phase 3 OPTIMISMM study: pomalidomide, bortezomib, and low-dose dexamethasone versus bortezomib and low-dose dexamethasone in relapsed or refractory multiple myeloma. Issue 8 (2nd July 2020) - Weisel, Katja; Dimopoulos, Meletios; Moreau, Philippe; Yagci, Munci; Larocca, Alessandra; Kanate, Abraham S.; Vural, Filiz; Cascavilla, Nicola; Basu, Supratik; Johnson, Peter; Byeff, Peter; Hus, Marek; et al.
Abstract: In the randomized phase-3 OPTIMISMM study, the addition of pomalidomide to bortezomib and low-dose dexamethasone (PVd) resulted in significant improvement in progression-free survival (PFS) in lenalidomide-pretreated patients with relapsed or refractory multiple myeloma (RRMM), including lenalidomide refractory patients. Here, we report health-related quality of life (HRQoL) results from this trial. Patients received PVd or Vd in 21-day cycles until disease progression or discontinuation. HRQoL was assessed using the EORTC QLQ-C30, QLQ-MY20, and EQ-5D-3L instruments on day 1 of each treatment cycle. Mean score changes for global QoL, physical functioning, fatigue, side effects of treatment domains, and EQ-5D-3L index were generally stable over time across treatment arms. The proportion of patients who experienced clinically meaningful worsening in global QoL and other domains of interest was similar. These HRQoL results with PVd along with previously demonstrated improvement in PFS vs Vd continue to support its use in patients with RRMM.